Virtual Digital Electronics Engineering Laboratory for Online learning after COVID19 - Thakor, Asifiqbal; Khant, Shailesh (Proceedings (International Conference on Reliability, Infocom Technologies and Optimization (Trends and Future Directions), 2024)
Nowadays learning aspects are changed after Covid19. Parents are attracted towards new trends of Online education. An attempt is made here for crating virtual laboratory in engineering education. This paper is intended to create awareness among under graduate and post graduate students of technical courses about virtual laboratories The most basic subject which has to be learn by computer science, Information Technology, electrical and electronics engineering students is Digital Electronics. Virtual experiments are created here which do not require any kind of real hardware. An online tool Tinkercad is used here to simulate the basic experiments of Digital Electronics Circuits. Some of the basic experiments like logic gates, Boolean functions implementation, combinational circuits and sequential circuits are simulated here. This virtual laboratory allows students to understand and grasp the experiments by their own at flexible time and at own speed. Even Faculties can develop the basic projects and allow students to perform it.